Transactions on petri nets and other models of concurrency V - Donatelli, Susanna; Kleijn, Jetty; Jensen, Kurt (Lecture Notes in Computer Science, 2012)
These Transactions publish archival papers in the broad area of Petri nets and other models of concurrency, ranging from theoretical work to tool support and industrial applications. ToPNoC issues are published as LNCS volumes, and hence are widely distributed and indexed. This Journal has its own Editorial Board which selects papers based on a rigorous two-stage refereeing process. ToPNoC contains: - Revised versions of a selection of the best papers from workshops and tutorials at the annual Petri net conferences - Special sections/issues within particular subareas (similar to those published in the Advances in Petri Nets series) - Other papers invited for publication in ToPNoC - Papers submitted directly to ToPNoC by their authors The fifth volume of ToPNoC contains revised versions of selected papers from workshops and tutorials held in conjunction with the 31st International Conference on Application and Theory of Petri Nets and Other Models of Concurrency, as well as a contributed paper selected through the regular submission track of ToPNoC. The 12 papers cover a diverse range of topics including model checking and system verification, synthesis, foundational work on specific classes of Petri nets, and innovative applications of Petri nets and other models of concurrency. Thus, this volume gives a good view of ongoing concurrent systems and Petri nets research.